2018
DOI: 10.1155/2018/2369430
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Ovarian Tumor in Mayer-Rokitansky-Küster-Hauser (MRKH) Syndrome

Abstract: In the most recent publications on Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, the uterine remnants and ovaries in patients may develop uterine remnant leiomyoma, adenomyosis, or ovarian tumor, and this can lead to problems in differential diagnosis. Here we summarize the diagnosis methods and available interventions for ovarian tumor in MRKH syndrome, with emphasis on the relevant clinical findings and illustrative relevant case. According to the clinical findings and illustrative relevant case, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Ovary anomalies are rare and only found in ~ 5–10% [ 3 , 13 , 101 ]. Different anomalies previously reported include unilateral agenesis, ectopic ovaries, polycystic ovaries, streak ovaries, and rarely tumors [ 102 ].…”
Section: Main Textmentioning
confidence: 99%
“…Ovary anomalies are rare and only found in ~ 5–10% [ 3 , 13 , 101 ]. Different anomalies previously reported include unilateral agenesis, ectopic ovaries, polycystic ovaries, streak ovaries, and rarely tumors [ 102 ].…”
Section: Main Textmentioning
confidence: 99%
“…Ovarian remnants neoplasms are rarely reported in these patients as they have normal ovarian development and function. A literature review by Miao et al (2018) [5] , collected few case reports of Mullerian ducts anomalies with various types of ovarian neoplasms, the majority of which were found to be benign after histopathological evaluation. Huepenbecker et al (2017) [6] , reported a rare occurrence of ovarian cystadenocarcinoma in two sisters affected by MRKH syndrome with normal 46XY karyotype and negative ovarian cancer genetic panel screening.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Mullerian dysgenesis syndrome have normal ovarian development. Few cases have been reported in the current literature about the development of uterine or ovarian tumors in patients with different classes of Mullerian dysgenesis but up to the authors’ best knowledge, there are no previous reports of ovarian tumor development in HWWS [5] , [6] , [7] . Thus, we report the first case of ovarian tumor development in HWWS.…”
Section: Introductionmentioning
confidence: 93%
“…The three most common methods of diagnosing MRKH syndrome are MRI, ultrasound, and laparoscopy [1,6]. However, in MRKH syndrome with a pelvic mass, imaging tools have limitations with respect to diagnosing the origin of the mass because of the indistinct uterus and abnormal anatomy [11]. In a review of 6 cases of MRKH syndrome with ovarian tumors, laparoscopy was shown to offer the possibility of concurrent diagnosis and treatment [11].…”
Section: Discussionmentioning
confidence: 99%